Replacement of humans in the classroom by artificial Intelligence: A rhetoric (Asian Journal of Educational Technology, 2023)
This study explores the probability if artificial intelligence can replace humans in the classroom. It identifies the limitations of artificial intelligence and the prevalence of human-level intelligence in education. Artificial intelligence is conceptualized and the research gaps in comparing artificial and human-level intelligence are identified. Comparative research method and explorative research design are adopted to guide this study. Secondary data is utilized with the use of a systematic desk research method and content analysis is used to explain the concepts and their relationship to each other. Three research objectives are used to assess human superiority to AI, identify limitations of AI and proffer measures to encourage collaboration between human-level and artificial intelligence. The study concludes and further provides recommendations necessary to support the relevance of human-level intelligence and AI in education.